C/EBPβ Promotes LPS-Induced IL-1β Transcription and Secretion in Alveolar Macrophages via NOD2 Signaling - Luo Y; Ge P; Wen H; Zhang Y; Liu J; Dong X; Lan B; Zhang G; Yang Q; Chen H (Dove Medical Press, 2022)
Yalan Luo,1- 3,* Peng Ge,1- 3,* Haiyun Wen,1- 3,* Yibo Zhang,1- 3 Jin Liu,1,3 Xuanchi Dong,1,3 Bowen Lan,1,3 Guixin Zhang,1- 3 Qi Yang,4 Hailong Chen1- 3 1Laboratory of Integrative Medicine, The First Affiliated Hospital of Dalian Medical University, Dalian, People's Republic of China; 2Institute (College) of Integrative Medicine, Dalian Medical University, Dalian, People's Republic of China; 3Department of General Surgery, The First Affiliated Hospital of Dalian Medical University, Dalian, People's Republic of China; 4Department of Traditional Chinese Medicine, The Second Affiliated Hospital of Dalian Medical University, Dalian, People's Republic of China*These authors contributed equally to this workCorrespondence: Qi Yang; Hailong Chen, Email dyeyyq1016@163.com; chenhailong@dmu.edu.cnObjective: C/EBPβ, a crucial transcription factor, regulates innate immunity and inflammatory responses. However, the role played by C/EBPβ in alveolar macrophage (AM) inflammatory responses remains unknown. This study aimed to investigate the role and mechanism of C/EBPβ in alveolar macrophages (AMs) from the transcriptional level and to search for natural compounds targeting C/EBPβ.Methods: Rat AMs were infected with Lv-sh-C/EBPβ and treated with LPS, and the expression levels of iNOS, TNF-α, IL-6, and IL-1β were measured by RT-qPCR, Western blotting, and ELISA. Mechanistically, transcriptome sequencing (RNA-seq) revealed changes in gene expression patterns in AMs after LPS stimulation and C/EBPβ knockdown. Functional enrichment analyses and rescue experiments identified and validated inflammation-associated cell signaling pathways regulated by C/EBPβ. Furthermore, virtual screening was used to search for natural compounds that inhibit C/EBPβ with the structure of helenalin as a reference.Results: Following stimulation with LPS, AMs exhibited an increased expression of C/EBPβ. C/EBPβ knockdown significantly decreased the expression levels of inflammatory mediators. A total of 374 differentially expressed genes (DEGs) were identified between LPS-stimulated C/EBPβ knockdown and negative control cells. The NOD-like receptor signaling may be a key target for C/EBPβ, according to functional enrichment analyses of the DEGs. Further experiments showed that the muramyl dipeptide (MDP, NOD2 agonist) reversed the downregulation of inflammatory mediators and the NF-κB pathway caused by the C/EBPβ knockdown. The virtual screening revealed that N-caffeoyltryptophan, orilotimod, and petasiphenone have comparable pharmacological properties to helenalin (a known C/EBPβ inhibitor) and demonstrate a great binding capacity to C/EBPβ.Conclusion: Ablation of C/EBPβ may attenuate LPS-induced inflammatory damage in AMs by inhibiting the NOD2 receptor signaling pathway. Three natural compounds, N-caffeoyltryptophan, orilotimod, and petasiphenone, may be potential C/EBPβ inhibitors.Graphical Abstract: Keywords: C/EBPβ, alveolar macrophage, RNA-seq, NOD-like receptor signaling pathway, IL-1β, virtual screening